Events, Urban Tourism and Cultural Appropriation: A Critical Perspective - Lotoaso, Renee; Faisal, Abrar (Auckland University of Technology, 2023)
Events in urban tourism destinations are continuously gaining prominence globally and are recognised to have substantial economic and socio-cultural impacts on countries, communities, and individuals. Despite this, the socio-cultural impacts of community events in urban destinations have not been widely researched. While the event industry and its different aspects have been extensively explored, there is a lack of literature on the cultural impacts of events and how cultural events in urban locations may impact local communities and their culture. This paper extensively reviews the literature pertaining to event impacts and offers a critical insight into the concepts and empirical findings on the significance and impacts of cultural events in urban destinations.
Keywords: Event impacts, cultural impacts, cultural festivals, cultural appropriation, urban tourism, urban destinations